Mangrove conservation awareness amongst shrimp culturist in Malaysia - Abdullah, Amin Mahir; Ismail, Mohd Mansor; Ng, Xin Khai; Darham, Suryani (Universiti Putra Malaysia Press, 2013)
Shrimp farming is an important industry in Malaysian agriculture. The growing domestic and export demands for the commodity have made shrimp farming expand over the years. However, intensive shrimp farming in Malaysia may result in substantial mangrove forest destruction as shrimp farms are mainly established in coastal mangrove forests. Thus, the objective of this paper is to ascertain the awareness of shrimp culturists in Peninsular Malaysia on the importance of mangroves conservation. Questionnaires were prepared using a 5-likert scale response option designed for a series of statements pertaining to the hypothetical environment and mangrove expected conditions in order to examine the understanding and perspective of the respondents toward environment issues. The data were analysed by exploratory factor analysis. The analysis uncovered four underlying environmental issues that are related to aquaculture production perceived by shrimp culturists. The shrimp culturists showed consistent attitude pertaining to the needs of conserving natural resources. Data on responses to this issue illustrated higher percentage on the importance of safeguarding the natural environment. The shrimp culturists, however, believed that aquaculture farming would not destruct mangrove area. The majority of shrimp culturists perceived that the introduction of new species into wild population would not harm natural food chain. As expected, farm waste was perceived to pollute areas surrounding the aquaculture farms. The study finds that, in general, the awareness among shrimp culturists on environment conservation issues is still low.